Audience interactivity with advertising applications in satellite TV via mobile devices - Hashim, Dr. Jafar Shaheed (Al-Adab Journal, 2020)
The research aims to achieve a number of objectives: 1- Reveal the extent of public interaction with the use of advertising applications in satellite tv via mobile devices 2- Identify audience preferences between applications 3- Find out the most important topics that the public prefers to interact with in advertising applications. 4- Reveal the most prominent obstacles facing users of advertising applications in satellite tv via mobile phone 5-To see how mobile satellite advertising applications contribute to increasing audience interaction . To achieve the objectives of the research, the researcher relied on the survey method by designing a questionnaire form, which included a number of axes and questions in order to obtain answers from the researchers, and extract the results, as the researcher used a sample of chance which is from the intentional samples, 250 forms were distributed among the questionnaires among the researchers in public places on both sides of Baghdad center (Al-Karkh and Al-Risafa), distributed among the researchers who use advertising applications in satellite satellite siphone exclusively, and retrieved (224). The researcher reached a number of conclusions, including: 1- The application of Al-Sharqiya channel was ranked first, followed by Sumerian channel in second place 2- The first benefit of using news applications is (speed of ad access), while the category (identifying products and services anywhere and anytime) has been resolved. 3- The problem (internet vulnerability) was one of the biggest obstacles suffered by application users, and then resolved (sudden exit from the application). As well as other results.